Spatial distribution of mangrove using a geographic information system in Aceh Besar. Issue 1 (February 2021) - Azhar, R; Rusdi, M; Irham, M; Fuadi, A
Abstract: The mangrove forest ecosystem is unique, both because of the subtract of siltation which results in less soil abrasion, high soil salinity, and experiencing a cycle of inundation by tides. Only a few plant species survive in such a place, and most of these species are unique to mangroves because they have undergone a process of adaptation and evolution. It is not widely known how far the mangrove areas are spread in Aceh. Therefore, research needs to be carried out with the aim of knowing the extent of the sustainability of mangrove management in terms of sediment characteristics. Information about the distribution, area and change of mangrove land cover can be determined by spatial analysis using a Geographical Information System (GIS) using ArcGIS. The method used in this research is the transect method and analysed based on the identification of mangrove species. Based on the analysis of the results of the study, it was identified that the mangrove species found in the research location of Peukan Bada sub-district (West Aceh Besar) consit of Rhizopora mucronata and Sonneratia alba, while the mangrove species found in Baitussalam (north Aceh Besar) were Rhizopora mucronata and Sonneratia alba . Meanwhile, based on observations with satellite imagery and location surveys, it was found that the mangroves in Baitussalam sub-district were denser and spread evenly than in the Peukan Bada area.